Exploring the physics of the sorkin-johnston state : renormalized stress-energy tensor, hadamard and energy conditions (2016)
The non-uniqueness of the vacuum state is one of the most characteristic features of the theory of quantum fields in curved backgrounds. Whereas in Minkowski spacetime the invariance with respect to Poincaré symmetry singles out the vacuum state, in general backgrounds there is no a priori given physical criterion on which the choice of a unique vacuum can rely. Recently, a construction for a new state has been proposed, which can be applied to a wide class of globally hyperbolic spacetimes. In view of potential applications to problems related to cosmology and black hole entropy, it is necessary to explore the physical and mathematical properties of this state, the Sorkin-Johnston state. This work focuses on the construction of a renormalized stress-energy tensor for the Sorkin-Johnston state on finite regions in 1+1 and 2+1 dimensional spacetimes. We consider cases with pseudo-periodic and Dirichlet boundary conditions in the spatial region. In each...